Cyber safety: a theoretical insight : in the framework of the project ‘The development of the observatory function of the European Centre of Expertise on Crime Prevention within the EUCPN’ -EUCPN Secretariat, February 2015, Brussels - Vanhee, Jorne (Theoretical paper, 2017)
This paper is written by the EUCPN Secretariat following the topic of the Estonian Presidency of the Network, which is Cyber Safety. It gives a theoretical insight in what Cyber Safety is. Furthermore, we take interest in what the exact object is of cybercrime and have a deeper look into two European policy priorities, namely cyber-attacks and payment fraud. Moreover, these priorities are the subject of the European Crime Prevention award. The goal of this paper is to add to the digital awareness of local policy-makers and practitioners on a theoretical level. A toolbox will follow with legislative measures, existing policies and best practices on this topic.